The Muftis dispositions and religious conservatism in Malaysia - Ab. Majid, Arfah (Global Academic Excellence, 2018)
The flourishing of Islamic cultures and lifestyles among Malaysian Muslim society in the form Islamic way of dressing, Islamic greetings and mushrooming of Islamic programs or events are perceived as manifestations of conservatism. Increased conservatism however is also associated with exclusive attitude, discrimination and persecution against the nonMuslims and other minority groups. The Islamic bureaucracy in Malaysia such as the SharÊÑah courts, National Fatwa Council and the Islamic Religious Department are deemed responsible for the creeping conservatism among Malaysian Muslim society. Present study therefore focuses on the Malaysian muftis since they are part of the bureaucracy. Apart from exploring the Muftis stances on few areas in order to measure their conservatism, this study also attempts to reassess the concept of conservatism itself. Six muftis have been interviewed including the Perlis Mufti, Penang Mufti, Perak Mufti, Federal Territories Mufti, Pahang Mufti and Melaka Mufti. This study proposes a revised concept of conservatism based on its theological underpinning. Theologically, conservatism denotes the idea of reliance on revelation and refutation of sole dependence on human reason in resolving issues and problems as propagated by Edmund Burke as a counter-response to the revolutionaries’ ideas. In the context of present study, conservatism implies the idea of preservation and upholding the original Islamic teachings that are based on the Qur’Én and Íadith. Conservatism therefore is not related to the negative attitudes and actions as commonly understood. Based on this concept of conservatism, the muftis’ dispositions could be categorized as conservative. They however differ in the manner of interpretation and contextualization of the revelation. Some of them are more progressive while some others are more traditional in their interpretations.